Conformational Aspects of Human Formyl-peptide Receptor Agonists - Dalpiaz, Alessandro; Vertuani, Gianni; Scatturin, Angelo; Vitali, Federica; Varani, Katia; Spisani, Susanna (Arzneimittelforschung, 2003)
The conformation of several Met-Ile-Phe-Leu analogues was analyzed using circular dichroism and infra-red absorption. Their effect on human neutrophils was verified by receptor binding assays and measurements of lysozyme release. The results demonstrate that in amphipatic environments the compounds examined can be highly and weakly ordered in β-turn structures, in dependence on their N-terminal substituents. The ability of the compounds to evoke neutrophil functions appears strongly and weakly influenced by N- and C-terminal modification, respectively.
Keywords: Circular dichroism; Formyl-peptide receptor agonists, chemotaxis; Human neutrophils; Peptide conformation